PENGARUH KEPEMIMPINAN GEMBALA DAN KETERLIBATAN ORGANISASI TERHADAP KOMITMEN ORGANISASI DI GEREJA LOKAL - Rumeksa, Edhy; Jonathans, Kornelius Rulli; Sarjono, Haryadi (The Way: Jurnal Teologi dan Kependidikan, 2025)
The decline in congregation commitment to remain rooted in the local church, as reported by the Bilangan Research Centre and Pew Research Centre, represents a significant challenge for churches in maintaining member engagement. Spiritual dissatisfaction is a key factor driving members to other churches. Church leaders play a crucial role in creating an environment that fosters commitment. Leadership marked by care and compassion strengthens the relationship between leaders and congregants, encouraging commitment through the example of Jesus as described in John 10:4. This study aims to examine the influence of shepherd leadership based on John 10:4 and organizational involvement on fostering organizational commitment in the local church, specifically at Gereja Bethel Indonesia (GBI) Light of The City. The research method involves a survey using a Likert scale, measuring organizational commitment with Allen and Meyer’s instrument, and organizational engagement using the Utrecht Work Engagement Scale (UWES). The results show that shepherd leadership based on the principles in John 10:4 and the level of congregational engagement play a role in building organizational commitment within the local church. Shepherd leadership, when applied contextually and relationally, can strengthen the congregation’s commitment to the church. However, the influence of shepherd leadership on organizational commitment is not direct, but is mediated by the level of organizational engagement among the congregants.